THE SEEKING OF STRATEGY WHERE IT IS NOT: TOWARDS A THEORY OF STRATEGY ABSENCE: A REPLY TO BAUERSCHMIDT - Inkpen, Andrew C. (Strategic Management Journal, 1996)
In this issue Bauerschmidt critiques a recent Strategic Management Journal paper dealing with the absence of strategy. In this paper (Inkpen and Choudhury, 1995), we argued that strategy absence should be viewed as a legitimate phenomenon of interest. Bauerschmidt maintained that we failed to instill a new strategy paradigm and challenged our arguments as a rhetorical ploy. Unfortunately, Bauerschmidt misinterpreted our intended message. Although we challenged the conventional wisdom that every firm must have an articulated strategy, instilling a new paradigm was not our objective. Our main argument was that the concept of absence may help strategy researchers better understand existing paradigms.